2015
DOI: 10.3109/11038128.2015.1057521
|View full text |Cite
|
Sign up to set email alerts
|

Client-centred practice: Perspectives of persons with a traumatic brain injury

Abstract: Occupational therapists are encouraged to value and invest in the development of relationships with clients whilst the importance of seeking and integrating the client perspective into practice and research is affirmed for the profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…Through this discourse and observation the IBITA instructors are building a picture of the person and the body's movement taking into consideration context and against the background of their professional knowledge. This perspective of person‐centered care is consistent with the literature with a particular focus on a flexible, individualized but collaborative approach to care while taking into consideration multiple aspects of the person's life Bobath reasoning approach:The theme Bobath reasoning approach is composed of 5 categories: (a) individualized assessment and treatment, (b) critical cues, (c) movement diagnosis, (d) activity/task/posture selection, and (e) reflective practice (Figure ). …”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Through this discourse and observation the IBITA instructors are building a picture of the person and the body's movement taking into consideration context and against the background of their professional knowledge. This perspective of person‐centered care is consistent with the literature with a particular focus on a flexible, individualized but collaborative approach to care while taking into consideration multiple aspects of the person's life Bobath reasoning approach:The theme Bobath reasoning approach is composed of 5 categories: (a) individualized assessment and treatment, (b) critical cues, (c) movement diagnosis, (d) activity/task/posture selection, and (e) reflective practice (Figure ). …”
Section: Resultssupporting
confidence: 68%
“…(Participant #16: Leslie) Through this discourse and observation the IBITA instructors are building a picture of the person and the body's movement taking into consideration context and against the background of their professional knowledge. This perspective of person-centered care is consistent with the literature with a particular focus on a flexible, individualizedbut collaborative approach to care while taking into consideration multiple aspects of the person's life [52][53][54]. iii.…”
supporting
confidence: 76%
“…Previous studies of clients' experiences in the context of rehabilitation after stroke have shown the importance of a good relationship and mutual trust between the therapist and the client [13][14][15][16][17][18][19]. The participants in D'Cruz and colleagues' study [16] understood client-centred practice as a process of engagement between the client and the therapist, where the client was valued and respected as a person [15]. Being actively engaged in the rehabilitation and especially in goal-setting [17,20] and decisionmaking [16] processes has been described as being crucial in rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…'s () results support the benefits of empathetic communication, especially within client‐centred practice. This study found that supportive client‐therapist relationships resulted in clients that were more engaged in their therapy and felt understood (D'Cruz et al .). The meaningful connection formed between therapist and client, was found to support clients to reconstruct their sense of self post‐brain injury.…”
Section: Discussionmentioning
confidence: 62%
“…According to the occupational therapy literature, effective communication is a key component in the provision of client‐centred practice (Borghi, Johnson, Barlascini, Moja & Vegni, ). Used appropriately, communication can help establish an emotional connection between therapists and their clients that enables the therapist to view the world through their clients’ eyes (D'Cruz, Howie & Lentin, ). This connection also encourages clients to share their challenges and fears with therapists, leading to an improved understanding of a client's disability and his/her world view (Sumsion & Law, ).…”
Section: Introductionmentioning
confidence: 99%